Prevalence, Diagnosis, and Vaccination Situation of Animal Chlamydiosis in China - Zhou, Jizhang; Li, Zhaocai; Lou, Zhongzi; Fei, Yuanyuan (Frontiers in Veterinary Science, 2018)
Since the first case of Chlamydia infection in duck had been reported in 1956 and the first case from domestic animal had been reported in 1979 in China, the chlamydia prevalence in China was heavily according to the published data. The Chlamydia in avian prevalence has been reported at least 11 provinces, Chlamydia in sheep and goats at least 11 provinces, in swine at least 15 provinces, in cows at least 13 provinces and in yaks at least 5 provinces with result of IHA detection. Different diagnostic method such as CFT, ELISA and ABC-ELISA (avidin-biotin-complex ELISA) had been established besides IHA. The inactivated vaccines have been developed with isolated strains from sheep, goats, swine and cows. These inactivated vaccines have been used since 1980s and Chlamydia prevalence in China has been successfully controlled in domestic animal. However, the inactivated vaccines of Chlamydia isolated from avian species have not been successful, although a series of experimental vaccine have been done. Due to the unsustainable eradication plan of Chlamydia in China, sporadic outbreak in animal would happen if the vaccinations were suspended and economy lose in some farmers Although Chlamydia prevalence in China has a long history, however, almost all published studies are in Chinese, which, in some degree, blocked scientists in other countries to understand the prevalence situation and control measures of Chlamydia in China.